The Extent to Which Professional Advice Can Reduce the Disposition Effect: An Emerging Market Study. (August 2018) - Bashall, James; Willows, Gizelle D.; West, Darron
This study tests for the disposition effect in South Africa across two classes of non-professional investors: those acting in their own capacity and those acting with the assistance of professional investment advisors. The trade history of 4, 840 investor accounts from a South African stockbroker was analysed over the 5-year period from October 2008 to October 2013. The results showed that individual investors in South Africa exhibit the disposition effect. However, investors acting with the assistance of professional advisors show the effect to a lesser extent which was found to be rationally justifiable on the grounds of portfolio rebalancing. JEL Classification: G11, G14, G40, G41